Analisis Pengaruh Kualitas Layanan, Inovasi, Citra Wisata Terhadap Minat Kunjung Ulang Dengan Daya Tarik Wisata Sebagai Variabel Intervening (Studi Pada Obyek Wisata Gunung Kemukus, Sragen, Jawa Tengah) - Permatasari, Racita (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the impact of service quality, innovation, tourist image, and tourist attraction on the revisit intention of visitors to Gunung Kemukus, Sragen, Central Java. A quantitative method was used in this study, with a purposive sampling technique to select 200 tourists who met specific criteria. Data collection was conducted through closed-ended questionnaires and documentation, while data analysis was performed using multiple linear regression. The results of the study indicate that service quality has a significant effect on the tourist attraction at Gunung Kemukus. This is evidenced by a t-value greater than the t-table (3.397 > 2.042) and a significance value smaller than 0.05 (0.000 < 0.05), with a positive regression coefficient of 0.354. This means that the better the service quality, the higher the tourist attraction. Innovation also has a significant impact on tourist attractions at Gunung Kemukus. The t-value is greater than the t-table (3.329 > 2.042), the significance value of 0.003 < 0.05, and a positive regression coefficient of 0.465 show that the innovation implemented by the management can enhance the tourist attraction of the site. Furthermore, the tourist image has a significant effect on tourist attraction, with a t-value greater than the t-table (3.806 > 2.042), significance value of 0.000 < 0.05, and a positive regression coefficient of 0.235. This indicates that a positive image of the tourist destination can increase its tourist attraction.